If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying b + c = 2b Solving b + c = 2b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-2b' to each side of the equation. b + -2b + c = 2b + -2b Combine like terms: b + -2b = -1b -1b + c = 2b + -2b Combine like terms: 2b + -2b = 0 -1b + c = 0 Add '-1c' to each side of the equation. -1b + c + -1c = 0 + -1c Combine like terms: c + -1c = 0 -1b + 0 = 0 + -1c -1b = 0 + -1c Remove the zero: -1b = -1c Divide each side by '-1'. b = c Simplifying b = c
| 6083.328=1/3B*25.6 | | 12a+b+18a+9b= | | 4sin^2x-5sinx+2cos^2x=0 | | 3(x+12)(x-12)=0 | | 4g^3/2g | | 15z/7=-8 | | H-19=-21 | | 3[x-6]+6=5x-6 | | v/10=5/7 | | 6038.328=(1/3)25.6B | | X^2-2x^2-48=0 | | 6038.328=(1/3)B*25.6 | | 2(5c-1)-2=7c+5 | | 2u/7=10 | | 6[3]+6x=3 | | (x-2)(x-(6+7i))(x-(6-7i))=0 | | (x^2)+10=0 | | 4x+2y+z=48 | | (x-5)+(12-6)= | | y=-16x^2+60x+40 | | -x^3*(4e^4x)+3x^2*e^4x=0 | | 6038.328=1/3B*25.6 | | (x-2)(x-(7+6i))(x-(7-6i))=0 | | y=-16t^2+60t+40 | | 10y-4x=5 | | 6m+500=625 | | 2(x^4)-200=0 | | 6038.328=1/3*B*25.6 | | 9x-x+6=0 | | 5x+12=10x+93 | | m^6-16m+64=0 | | 2715.904=1/3*424.36h |